The Benefits of Picture Storybooks in Helping Children Recognize Their Emotions from an Early Age - Purnawarman, Farah Amani Hessa Hasana; Resmisari, Ganis (PT Ininnawa Paramacitra Edukasi, 2025)
Feelings are emotional experiences that we experience in response to events, people, or situations. Feelings can be positive or negative. Recognizing our own feelings is very important so that we can understand ourselves and others well, build good relationships with others, solve problems better, and improve our quality of life. Unfortunately, the prevailing culture and social norms are obstacles for most Indonesian people to recognize, understand, and express their own feelings, especially from an early age. Therefore, efforts are needed to help children recognize and understand their feelings from an early age. One way is through picture story books. This study discusses the theories of the importance of recognizing and understanding feelings from an early age, the benefits of picture story books for children, and an analysis of the results from the researcher’s questionnaire about the people’s perception and awareness of the importance of education for children to recognize and understand their feelings from an early age. This study uses a qualitative approach in the form of a literature study and a quantitative approach by distributing questionnaires to 108 adolescent and adult respondents.